Validation of stay-green and stem reserve mobilization QTLs: physiological and gene expression approach - Taria, Sukumar; Arora, Ajay; Kumar, Sudhir; Krishna, Hari; Meena, Shashi; Singh, Biswabiplab; China Malakondaiah, Animireddy; S., Kousalya; Padaria, Jasdeep Chatrath; Singh, Pradeep Kumar; Alam, Badre; Kumar, Sushil; et al. (Frontiers in Plant Science, 2025)
IntroductionAbiotic stress significantly reduces the wheat yield by hindering several physiological processes in plant. Stay-green (SG) and stem reserve mobilization (SRM) are the two key physiological traits, which can contribute significantly to grain filling during stress period. Validation of genomic regions linked to SG and SRM is needed for its subsequent use in marker-assisted selection in breeding program.MethodsUsing a physiological and gene expression approach, quantitative trait loci (QTLs) for stay-green (SG) and stem reserve mobilization (SRM) were validated in a pot experiment study using contrasting recombinant inbred lines including its parental lines (HD3086/HI1500) in wheat. The experiment was laid down in a completely randomized design under normal (control, drought) and late sown (heat and combined stress) conditions during the 2022-2023 rabi season. Drought stress was imposed by withholding irrigation at the anthesis stage, whereas heat stress was imposed by 1-month late sowing compared to the normal sowing condition. Combined stress was imposed by 1-month late sowing along with restricted irrigation at the flowering stage. Superior lines (HDHI113 and HDHI87) had both SG and SRM traits, whereas inferior lines (HDHI185 and HDHI80) had contrasting traits, i.e., lower SG and SRM traits. HD3086 and HI1500 had SG and SRM traits respectively. Potential candidate genes were identified based on the flanking markers of the mapped QTLs using the BioMart tool in the Ensembl Plants database to validate the identified QTLs. Real-time gene expression was conducted with SG-linked genes in the flag leaf and SRM-linked genes in the peduncle.Results and DiscussionIn this study, HDHI113 and HDHI87 showed higher expression of SG-related genes in the flag leaf under stress conditions. Furthermore, HDHI113 and HDHI87 maintained higher chlorophyll a content of 7.08 and 6.62 mg/gDW, respectively, and higher net photosynthetic rates (PN) of 17.18 and 16.48 µmol CO2/m2/s, respectively, under the combined stress condition. However, these lines showed higher expression of SRM-linked genes in the peduncle under drought stress, indicating that drought stress aggravates SRM in wheat. HDHI113 and HDHI87 recorded higher 1,000-grain weights and spike weight differences under combined stress, further validating the identified QTLs being linked to SG and SRM traits. Henceforth, the identified QTLs can be transferred to developed wheat varieties through efficient breeding strategies for yield improvement in harsh climate conditions.